Use of sodium‐glucose co‐transporter‐2 inhibitors in patients with type 2 diabetes mellitus and multiple cardiovascular risk factors: An Asian perspective and expert recommendations. Issue 11 (17th July 2019) - Deerochanawong, Chaicharn; Chan, Siew P.; Matawaran, Bien J.; Sheu, Wayne H.‐H.; Chan, Juliana; Man, Nguyen H.; Suastika, Ketut; Khoo, Chin M.; Yoon, Kun‐Ho; Luk, Andrea; Mithal, Ambrish; Linong, Ji
Abstract: Diabetes mellitus in Asia accounts for more than half of the global prevalence. There is a high prevalence of cardiovascular disease (CVD) in the region among people with type 2 diabetes mellitus (T2DM) and it is often associated with multiple risk factors including hypertension, renal disease and obesity. The early onset of T2DM and the eventual long disease duration portends an increasing proportion of the population to premature CVD. In addition to lowering blood glucose, sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitors exert favourable effects on multiple risk factors (including blood pressure, body weight and renal function) and provide an opportunity to reduce the risk of CVD in patients with T2DM. In this article, we consolidated the existing literature on SGLT‐2 inhibitor use in Asian patients with T2DM and established contemporary guidance for clinicians. We extensively reviewed recommendations from international and regional guidelines, published data from clinical trials in the Asian population (dapagliflozin, canagliflozin, empagliflozin, ipragliflozin, luseogliflozin and tofogliflozin), CVD outcomes trials (EMPAREG‐OUTCOME, CANVAS and DECLARE‐TIMI 58) and real‐world evidence studies (CVD‐REAL, EASEL, CVD‐REAL 2 and OBSERVE‐4D). A series of clinical recommendations on the use of SGLT‐2 inhibitors in Asian patients with T2DM was deliberated among experts with multiple rounds of review and voting. Based on the available evidence, we conclude that SGLT‐2 inhibitors represent an evidence‐based therapeutic option for the primary prevention of heart failure hospitalization and secondary prevention of CVD in patients with T2DM, and should be considered early on in the treatment algorithm for patients with multiple risk factors, or those with established CVD.